“That's just typical!” A qualitative video review study on the ecological validity of couples' stress conversations in the lab - Weitkamp, Katharina; Constam, Jasmin; Bodenmann, Guy (Frontiers in Psychology, 2025)
ObjectiveFor research on dyadic coping—how partners in intimate relationships deal with stress together—video-recorded behavioral observations in a lab are considered to be the best way to study actual coping behavior interactions. To date, little is known about the ecological validity of these laboratory situations. The current study aimed to ask couples directly what they considered to be typical when looking back at a videotaped behavioral interaction sequence in the lab.MethodsA qualitative video recall approach was used in which interview data were collected. N = 117 couples participated in a videotaped stress communication in a lab setting and were subsequently separately interviewed in a video-review task on the typicality of the lab situation and their partner's behavior. Interviews were audiotaped and analyzed using qualitative content analyses.ResultsParticipants mostly viewed their partner's behavior as typical. However, the setting and the course of the conversation were viewed as less typical. There were gender and age differences with regards to the ecological validity of lab settings.Conclusions and implicationsResults indicate that the ecological validity of dyadic coping in the laboratory is multidimensional. The lab setting seems comparable to situations where both partners have time and are not stressed.